Genetic marker suitable for identification and genotyping of Plasmodium ovale curtisi and Plasmodium ovale wallikeri. - Tanomsing, N; Imwong, M; Sutherland, C; Dolecek, C; Hien, T; Nosten, F; Day, N; White, N; Snounou, G (2013)
We present a seminested PCR method that specifically discriminates between Plasmodium ovale curtisi and P. ovale wallikeri with high sensitivity. The test is based on species-specific amplification of a size-polymorphic fragment of the tryptophan-rich antigen gene, potra, which also permits discrimination of intraspecific sequence variants at this locus.